2009
DOI: 10.1021/cg901062n
|View full text |Cite
|
Sign up to set email alerts
|

Structural Features, Phase Relationships and Transformation Behavior of the Polymorphs I−VI of Phenobarbital

Abstract: Six of the more easily accessible forms of phenobarbital (Pbtl-I, II, III, IV, V, VI) were characterized by a variety of analytical methods (thermal analysis, solution calorimetry, X-ray diffraction methods, infrared, Raman and solid-state NMR spectroscopy), in order to get a clear picture of this complex polymorphic system and to eliminate severe inconsistencies in the existing data. On the basis of the thermochemical data and stability studies, we were able to clarify the thermodynamic relationships of the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
37
0
3

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(41 citation statements)
references
References 51 publications
1
37
0
3
Order By: Relevance
“…Experimental solid-state NMR data under magic angle spinning (MAS) conditions were taken from the literature. CSD reference codes and citations to the experimental data for each crystal are given as follows: Acetaminophen: 27,80 form I (HXACAN26 81 ), form II (HXACAN23 82 ), and form III (HXACAN29 83 ); Phenobarbital: 19 form II (PHBARB06 84 ) and form III (PHBARB09 85 ); Testosterone: 17 α form (TESTON10 86 ) and β (monohydrate) form (TESTOM01 87 ).…”
Section: Computational Methodsmentioning
confidence: 99%
“…Experimental solid-state NMR data under magic angle spinning (MAS) conditions were taken from the literature. CSD reference codes and citations to the experimental data for each crystal are given as follows: Acetaminophen: 27,80 form I (HXACAN26 81 ), form II (HXACAN23 82 ), and form III (HXACAN29 83 ); Phenobarbital: 19 form II (PHBARB06 84 ) and form III (PHBARB09 85 ); Testosterone: 17 α form (TESTON10 86 ) and β (monohydrate) form (TESTOM01 87 ).…”
Section: Computational Methodsmentioning
confidence: 99%
“…The escaping of NMP molecules led to the changes in packing and conformation . With increasing temperature, molecular restriction and heterogeneous nucleation of SD occurred on the surface of the particle . As the temperature continued to rise, the fine grains grew rapidly.…”
Section: Resultsmentioning
confidence: 99%
“…It is shown that compound 1 displays bluish violet fluorescence emission in these aprotic or protic solvents in a region of 325-337 nm. Since it is difficult to oxidize or reduce the Cd(II) cations due to their d 10 configuration [42][43][44] , the origin of the emission for compound 1 is neither metal-to-ligand charge transfer(MLCT) nor ligand-to-metal charge transfer(LMCT). The intense fluorescent emission of compound 1 is attributed to the intraligand π * →π transition of mpda ligand.…”
Section: Spectral Behavior Of Compound 1 In Different Solventsmentioning
confidence: 99%